2016 Intl IEEE Conferences on Ubiquitous Intelligence &Amp; Computing, Advanced and Trusted Computing, Scalable Computing and C 2016
DOI: 10.1109/uic-atc-scalcom-cbdcom-iop-smartworld.2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Lite: A Lightweight Semantic Model for the Internet of Things

Abstract: Over the past few years the semantics community\ud has developed ontologies to describe concepts and relationships\ud between different entities in various application domains,\ud including Internet of Things (IoT) applications. A key problem\ud is that most of the IoT related semantic descriptions are not\ud as widely adopted as expected. One of the main concerns\ud of users and developers is that semantic techniques increase\ud the complexity and processing time and therefore they are\ud unsuitable for dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(77 citation statements)
references
References 10 publications
0
74
0
3
Order By: Relevance
“…In the same context, authors in [8] tried to examine how the IoT methods can be demonstrated utilizing web ontologies that enable them to straightforwardly convey the strategy usage. On the other hand, authors in [9] propose an IoT-Lite ontology, by launching of the semantic sensor organize (SSN) ontology to depict key IoT ideas permitting interoperability and revelation of tactile information in heterogeneous IoT stages by a lightweight semantics. In addition to that, authors In [10] established a more concluded method for collecting sensor information by using SASML (Sensors Annotation and Semantic Mapping Language) to annotate the corresponding relationship between the SSN ontology and its sensor data in the mapping file using the RDF Mapping Data Sensor (SDRM) algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same context, authors in [8] tried to examine how the IoT methods can be demonstrated utilizing web ontologies that enable them to straightforwardly convey the strategy usage. On the other hand, authors in [9] propose an IoT-Lite ontology, by launching of the semantic sensor organize (SSN) ontology to depict key IoT ideas permitting interoperability and revelation of tactile information in heterogeneous IoT stages by a lightweight semantics. In addition to that, authors In [10] established a more concluded method for collecting sensor information by using SASML (Sensors Annotation and Semantic Mapping Language) to annotate the corresponding relationship between the SSN ontology and its sensor data in the mapping file using the RDF Mapping Data Sensor (SDRM) algorithm.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few other research projects on the IoT semantic framework are: (i) the Open-IoT project relies on a blueprint cloud-based IoT architecture, which leverages the W3C SSN ontology for modeling sensors [13]. (ii) The IoT-Lite ontology [14] is an instantiation of the semantic sensor network (SSN) ontology to describe key IoT concepts allowing interoperability, discovery of sensory data in heterogeneous IoT platforms by lightweight semantics. This project was deployed to address the concern that semantic techniques increase the complexity and the processing time.…”
Section: Related Workmentioning
confidence: 99%
“…In this way, after applying the action, the algorithm calls shop2mt with these possibilities (lines [18][19][20]. If w is a method, we perform the task decomposition (lines [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. If more than one decomposition is applied, a new thread is generated for each of the possibilities (lines 27-32).…”
Section: The Automatic Service Composermentioning
confidence: 99%